Thumb sucking habit: mechanism and dimensions - A Khavari (Tehran University of Medical Sciences, 1989)
Thumb sucking is a harmful prevalent habit among children that has been identified since 70 years B.C. and causes many dentoalveolar disorders affecting both intra and extra oral soft tissues. This habit is harmful in many aspects for the children and even their environment but is not considered as an addiction according to its special features. In thumb sucking habit, both the finger and oral surrounding contribute to the habit by specific mechanism. Moreover, Duration, Frequency and intensity are effective factors that compensate the effects of each other by replacing the decreased reflex. Some Scientists believe this compensation is accidental. As a conclusion, the cooperation of these factors can increase the harmful effects of thumb sucking.